Smart fibres, fabrics and clothing - Tao, Xiaoming (CRC Press ; Woodhead Pub., 2001)
This important book provides a guide to the fundamentals and latest developments in smart technology for textiles and clothing. The contributors represent a distinguished international panel of experts and the book covers many aspects of cutting edge research and development.
Published in association with The Textile Institute.
Keywords: Textile fibers.; Textile chemistry.; Textile fabrics.; Smart materials.; elektronické knihy; electronic books